Cluster C maladaptive personality traits in a general population of adolescents - Fonseca-Pedrero, Eduardo; Paino, Mercedes; Lemos-Giráldez, Serafín; Muñiz, José (Actas Españolas de Psiquiatría, 2013)
Introduction. The prevalence of the Cluster C traits and personality disorders in adolescents has been poorly analyzed. The main goal of this research was to analyze the rate of the Cluster C traits and maladaptive personality patterns in a community sample of adolescents. We also examined the dimensional structure and the influence of sex and age in its phenotypic expression. Method. The sample comprised a total of 1443 participants (48.2% male) with a mean age of 15.92 years (SD = 1.18). We used the Cluster C subscales of the Personality Diagnostic Questionnaire-4 + (PDQ-4+). Results. The results showed that the traits of personalities “anxious” or “inhibited” are common among adolescents. As the cut-offs PDQ-4+, 28.3% of the sample showed at least one maladaptive personality pattern of Cluster C. The analysis of the internal structure of the items yielded a onedimensional solution called Inhibited-Anxious personality. We found statistically significant differences by gender in mean scores in the Avoidant subscale and by age in the Dependent subscale. Conclusions. These data yield new clues that improve the understanding of the Cluster C traits and maladaptive patterns of personality in this sector of the population.